Hydrogen production model: a computational approach to optimize cost reduction strategies, environmental impact, and financial viability - Fairuz Wasima; Md. Sanowar Hossain; Abdullah Mohammad Tousiful Hoque Chy; Monjur Mourshed; Md. Golam Kibria (Energy Conversion and Management: X)
This study presents a comprehensive techno-economic and environmental evaluation of hydrogen production from organic waste feedstocks in Bangladesh, utilizing an integrated approach through advanced modelling tools. The research combines H2A (Hydrogen Production Cost Analysis), HDSAM (Hydrogen Delivery Scenario Analysis Model), and H2FAST (Hydrogen Financial Assessment Tool) to assess the feasibility of large-scale hydrogen production, distribution, and storage. H2A is employed to analyze hydrogen production costs, considering various feedstocks and production methods, while HDSAM evaluates the delivery pathways and logistics of liquid and gaseous hydrogen. H2FAST is used to perform detailed financial modelling, focusing on investment risks, profitability, and financial metrics of hydrogen projects. This integrated methodology provides a comprehensive analysis of the hydrogen value chain, addressing key factors such as production costs, logistics, and financial feasibility. Main results of the study indicate that hydrogen production costs can range from $2.16/kg to $2.18/kg depending on feedstock efficiency and plant utilization. Financial assessments show that larger-scale hydrogen stations (4,000 kg/day) benefit from economies of scale, with hydrogen costs dropping to approximately $8.51/kg, compared to $12.75/kg for smaller stations (400 kg/day). The study concludes incorporates region-specific data for Bangladesh, addressing local challenges such as infrastructure limitations, financial constraints, and energy demands, offering a tailored analysis that can inform future hydrogen projects in Bangladesh and similar developing economies.